Acidic ammonium salt coated ternary positive electrode material and preparation method thereof, and lithium ion battery

By using acidic ammonium salt as a coating additive, combined with high-temperature sintering and two-stage calcination processes, the problem of uneven coating of ternary cathode materials is solved, an efficient coating effect is achieved, and the cycle stability and performance of lithium-ion batteries are improved. Safety performance.

CN117976889BActive Publication Date: 2025-01-21SHENZHEN ORI TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410391213.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-02
Publication Date
2025-01-21
Estimated Expiration
2044-04-02

AI Technical Summary

Technical Problem

The existing ternary positive electrode materials have particle agglomeration during the coating process, resulting in uneven coating, which cannot effectively suppress side reactions caused by contact with the electrolyte, affecting the cycle stability and safety performance of the battery.

Method used

Acidic ammonium salt is used as the coating additive, and through high-temperature sintering and two-stage calcination processes, uniform coating of the ternary cathode material is achieved. The acidic ammonium salt reacts with Li2CO3 and LiOH on the surface of the diburn material to reduce the residual alkali content and ensure the uniformity of the coating additives through ball milling.

Benefits of technology

It achieves uniform coating of the ternary cathode material, reduces the residual alkali content, improves the cycle stability and safety performance of the battery, and reduces production costs and energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117976889B_ABST
    Figure CN117976889B_ABST
Patent Text Reader

Abstract

The present invention relates to an acidic ammonium salt-coated ternary positive electrode material and a preparation method thereof, and a lithium ion battery. The preparation method comprises the following steps: S1, after a ternary precursor and lithium hydroxide monohydrate are uniformly mixed in a high-speed mixer, high-temperature sintering is performed in a pure oxygen atmosphere to obtain a first-fired material; S2, after a first-fired material and a dopant are uniformly mixed in a high-speed mixer, high-temperature sintering is performed in a pure oxygen atmosphere to obtain a second-fired material; S3, a coating additive is ball-milled to obtain a powdered coating additive, wherein the coating additive is an acidic ammonium salt; S4, the second-fired material and the coating additive are uniformly stirred by a coating device; S5, the mixture in S4 is subjected to two-stage calcination, low-temperature calcination, and then the temperature is increased for high-temperature calcination to obtain an acidic ammonium salt-coated ternary positive electrode material. The acidic ammonium salt-coated ternary positive electrode material provided by the present invention is uniformly coated, has a good coating effect, and improves the cycle stability of the lithium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion battery materials, and in particular to an acidic ammonium salt-coated ternary positive electrode material and a preparation method thereof, and a lithium ion battery. Background Art

[0002] Lithium-ion batteries have the advantages of high energy density, high operating voltage, and long cycle life. They are widely used in many new energy fields such as portable electronic devices and electric vehicles. In practical applications, the cycle performance, rate performance, and safety performance of high-nickel ternary materials need to be improved. Positive electrode materials are key factors affecting the performance and cost of lithium-ion batteries. With the development of the new energy vehicle industry, high-nickel ternary positive electrode materials have become a research hotspot due to their advantages such as high specific capacity and low cost, and are considered to be very promising power battery materials. However, high-nickel ternary materials also have some disadvantages. For example, there are a large amount of lithium hydroxide monohydrate and lithium carbonate on the surface of the material, which are easy to react with the electrolyte to cause the dissolution of metal ions. At the same time, safety problems such as flatulence may occur during battery processing and use.

[0003] The existing ternary cathode materials have a high residual alkali content, which affects the cycle stability of the battery. Surface coating is a common modification method that can inhibit the side reactions generated by the contact between the cathode material and the electrolyte, so that the material maintains a relatively stable structure. The commonly used coating methods are divided into liquid phase and solid phase coating. The liquid phase method has a complex process and high requirements for production machines in the industrial production process, and the liquid recovery and treatment used for coating increases additional production costs; while the current solid phase method has high requirements for the particle size of the coating material, and solid phase particles are prone to agglomeration during the mixed coating process with the ternary cathode material, resulting in uneven coating, the coating material fails to make good contact with the ternary material, and the coating effect is not ideal; a higher heat treatment temperature is required, resulting in higher energy consumption.

[0004] Therefore, the existing technology needs to be improved. Summary of the invention

[0005] In the prior art, the current solid phase method has high requirements on the particle size of the coating material, and solid phase particles are prone to agglomeration during the mixed coating process with the ternary positive electrode material, resulting in uneven coating. The coating material fails to make good contact with the ternary material and the coating effect is not ideal. Therefore, the present invention provides an acidic ammonium salt coated ternary positive electrode material and a preparation method thereof, and a lithium ion battery for solving the above problems.

[0006] To achieve the above object, in a first aspect, the present invention provides a method for preparing an acidic ammonium salt-coated ternary positive electrode material, which comprises the following specific steps:

[0007] S1. After the ternary precursor and lithium hydroxide monohydrate are uniformly mixed in a high-speed mixer, high-temperature sintering is performed in a pure oxygen atmosphere to obtain a single-fired material;

[0008] S2, mixing the first-fired material and the dopant in a high-speed mixer, and then sintering at a high temperature in a pure oxygen atmosphere to obtain a second-fired material;

[0009] S3, ball-milling the coating additive to obtain a powdered coating additive, wherein the coating additive is an acidic ammonium salt, and the coating additive includes any one of ammonium molybdate, ammonium dihydrogen phosphate, ammonium fluoride, and ammonium niobium oxalate;

[0010] S4, stirring the sintered material in S2 and the coating additive in S3 uniformly through a coating device;

[0011] S5. The mixed material in S4 is subjected to two-stage calcination. After low-temperature calcination, the temperature is increased to perform high-temperature calcination to obtain an acidic ammonium salt-coated ternary positive electrode material.

[0012] In one implementation, in S1, the ternary precursor is Ni a Co b Mn 1-a-b (OH)2 or Ni a Co b Mn c X 1-a-b-c (OH)2, wherein a, b, c are any numbers between 0 and 1, and X is a doping element, including any one of Nb, Zr, Cr, Mo, Ti, W and V.

[0013] In one implementation, in S1, the ternary precursor and lithium hydroxide monohydrate are added in a ratio of Li / (Ni+Co+Mn) of 1.00-1.05.

[0014] In one implementation, in S2, the content of the dopant is 0.2 wt% to 2 wt%.

[0015] In one implementation, in S1, the high temperature sintering is 400°C~600°C, and the sintering time is 6h~12h; in S2, the high temperature sintering is 400°C~1000°C, and the sintering time is 6h~12h.

[0016] In one implementation, in S3, the ball milling time of the coating additive is 30 min to 120 min, the ball milling speed is 500 rpm to 1500 rpm, and the content of the coating additive is 0.2 wt% to 2 wt%.

[0017] In one implementation, in S4, the coating equipment is any one of a high-speed mixer, a plowshare mixer, a ribbon mixer and a conical mixer.

[0018] In one implementation, in S5, the low-temperature calcination temperature ranges from 200°C to 300°C, and the low-temperature calcination time is 4h to 6h; the high-temperature calcination temperature ranges from 400°C to 800°C, and the high-temperature calcination time is 6h to 12h.

[0019] In a second aspect, the present invention further provides an acidic ammonium salt-coated ternary positive electrode material, which is prepared by any one of the above-mentioned methods for preparing the acidic ammonium salt-coated ternary positive electrode material.

[0020] In a third aspect, the present application also provides a lithium-ion battery, which includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet includes the above-mentioned acidic ammonium salt-coated ternary positive electrode material.

[0021] Beneficial effects: In the preparation method of the acidic ammonium salt-coated ternary positive electrode material provided by the present invention, by adding the acidic ammonium salt as a coating additive, the acidic ammonium salt can undergo an acid-base neutralization reaction with the Li2CO3 and LiOH remaining on the surface of the di-sintered material, thereby effectively reducing the residual alkali of the di-sintered material; the coating additive can be evenly mixed after ball milling for sintering and coating; the added acidic ammonium salt has a low melting point, so that the coating additive can be converted into a liquid at a lower temperature of the second-stage calcination, and the liquid coating additive is evenly distributed on the surface of the ternary positive electrode material in a film-like morphology, which can achieve maximum coating coverage, make the coating uniform, improve its coating effect, and improve the cycle stability of the lithium-ion battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The residual alkali composition and content of the acidic ammonium salt-coated ternary positive electrode material provided in Examples 1-3 and Comparative Example 1 of the present invention;

[0023] Figure 2 Residual alkali composition and content of the acidic ammonium salt-coated ternary positive electrode material provided in Examples 4-5 and Comparative Example 2

[0024] Figure 3 This is a SEM image of the acidic ammonium salt-coated ternary positive electrode material provided in Example 1 of the present invention;

[0025] Figure 4 This is a SEM image of the acidic ammonium salt-coated ternary positive electrode material provided in Example 2 of the present invention;

[0026] Figure 5 This is a SEM image of the acidic ammonium salt-coated ternary positive electrode material provided in Example 3 of the present invention;

[0027] Figure 6This is a SEM image of the acidic ammonium salt-coated ternary positive electrode material provided in Example 4 of the present invention;

[0028] Figure 7 This is a SEM image of the acidic ammonium salt-coated ternary positive electrode material provided in Example 5 of the present invention;

[0029] Figure 8 This is a SEM image of the acidic ammonium salt-coated ternary positive electrode material provided in Comparative Example 1 of the present invention;

[0030] Fig. 9 This is the SEM image of the acidic ammonium salt-coated ternary positive electrode material provided in Comparative Example 2 of the present invention.

[0031] Fig.10 This is an EDS test chart of the Mo element of the acidic ammonium salt-coated ternary positive electrode material provided in Example 1 of the present invention;

[0032] Fig.11 This is an EDS test chart of the P element of the acidic ammonium salt-coated ternary positive electrode material provided in Example 2 of the present invention;

[0033] Fig.12 This is an EDS test chart of the F element of the acidic ammonium salt-coated ternary positive electrode material provided in Example 3 of the present invention;

[0034] Fig.13 EDSceshi diagram of the Mo element of the acidic ammonium salt-coated ternary cathode material provided in Example 4 of the present invention;

[0035] Fig.14 This is an EDS test chart of the P element of the acidic ammonium salt-coated ternary positive electrode material provided in Example 5 of the present invention;

[0036] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0037] In order to make the purpose, technical solutions and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the accompanying drawings and examples. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the description of the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" described below means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms is not necessarily for the same embodiment or example. Moreover, the technical features involved in each embodiment of the present invention can be combined with each other as long as they do not conflict with each other.

[0038] The present invention provides a method for preparing an acidic ammonium salt-coated ternary positive electrode material, which comprises the following specific steps:

[0039] S1. After the ternary precursor and lithium hydroxide monohydrate are uniformly mixed in a high-speed mixer, high-temperature sintering is performed in a pure oxygen atmosphere to obtain a single-fired material;

[0040] S2, mixing the first-fired material and the dopant in a high-speed mixer, and then sintering at a high temperature in a pure oxygen atmosphere to obtain a second-fired material;

[0041] S3, ball-milling the coating additive to obtain a powdered coating additive, wherein the coating additive is an acidic ammonium salt, and the coating additive includes any one of ammonium molybdate, ammonium dihydrogen phosphate, ammonium fluoride, and ammonium niobium oxalate;

[0042] S4, stirring the sintered material in S2 and the coating additive in S3 uniformly through a coating device;

[0043] S5. The mixed material in S4 is subjected to two-stage calcination. After low-temperature calcination, the temperature is increased to perform high-temperature calcination to obtain an acidic ammonium salt-coated ternary positive electrode material.

[0044] Specifically, in S1, the ternary precursor is a nickel-cobalt-manganese ternary precursor, and its chemical formula is Ni a Co b Mn 1-a-b (OH)2 or Ni a Co b Mn c X 1-a-b-c (OH)2, wherein a, b, c are any numbers between 0 and 1, and X is a doping element, including any one of Nb, Zr, Cr, Mo, Ti, W and V. When the ternary precursor is Ni a Co b Mn c X 1-a-b-c (OH)2, in the subsequent steps, the dopant added is the oxide of the doping element X in the ternary precursor. Furthermore, the addition ratio of Li / (Ni+Co+Mn) in the ternary precursor and lithium hydroxide monohydrate is 1.00~1.05. In S1, the high-temperature sintering is 400℃~600℃, and the sintering time is 6h~12h. In this step, a preliminary one-sintered material of lithium ion positive electrode material is obtained by high-temperature calcination.

[0045] Specifically, in S2, the mixture of the first-fired material and the dopant is calcined at high temperature in a pure oxygen atmosphere, wherein the high-temperature sintering is 400°C to 1000°C, the sintering time is 6h to 12h, and the dopant is an oxide of a doping element, i.e., an oxide of any one of elements such as Nb, Zr, Cr, Mo, Ti, W and V. Further, the content of the dopant is 0.2wt% to 2wt%. The purpose of mixing the first-fired material and the dopant uniformly and then sintering at high temperature is to obtain a second-fired material, thereby improving the performance of the positive electrode material.

[0046] Specifically, in S3, the coating additive is milled for 30 min to 120 min, the milling speed is 500 rpm to 1500 rpm, and the content of the coating additive is 0.2 wt% to 2 wt%. After the ball milling treatment, a powdered coating additive is obtained, which will be used to coat the ternary positive electrode material in the subsequent steps.

[0047] Specifically, in S4, the coating device is any one of a high-speed mixer, a plowshare mixer, a ribbon mixer and a conical mixer. The coating device is used to evenly mix the sintered material and the coating additive, so that the coating additive can be evenly coated on the surface of the sintered material.

[0048] Specifically, in S5, the low-temperature calcination temperature ranges from 200°C to 300°C, and the low-temperature calcination time is 4h to 6h; the high-temperature calcination temperature ranges from 400°C to 800°C, and the high-temperature calcination time is 6h to 12h. After low-temperature calcination and high-temperature calcination, the acidic ammonium salt-coated ternary positive electrode material is obtained, thereby improving the performance and stability of the positive electrode material. Among them, the two-stage calcination does not need to maintain a high heat treatment temperature all the time, which can reduce energy consumption and reduce production costs.

[0049] The present invention also provides a lithium ion battery, which includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet includes the above-mentioned acidic ammonium salt-coated ternary positive electrode material. Wherein, the positive electrode sheet includes a positive electrode current collector and a positive electrode active layer arranged on the surface of the positive electrode current collector, and the positive electrode active layer includes the above-mentioned acidic ammonium salt-coated ternary positive electrode material, a conductive agent and a binder. There are no special requirements for the selection of conductive agents and binders, and they can be conventionally selected in the art. For example, the conductive agent is selected from at least one of conductive carbon black, acetylene black, Ketjen black, conductive graphite, conductive carbon fiber, carbon nanotubes, single-walled carbon nanotubes, multi-walled carbon nanotubes, and carbon fibers, and the binder is selected from at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), and polyacrylate lithium (PAALi).

[0050] In the preparation process of lithium-ion batteries, the positive electrode active material, conductive agent and binder are first mixed in a certain proportion and dispersed in a solvent, generally NMP, and stirred evenly to obtain a slurry of the positive electrode active material; secondly, the slurry of the positive electrode active material is evenly coated on the positive electrode current collector, generally the surface of aluminum foil, and dried to form a positive electrode active material layer; finally, the positive electrode sheet is obtained by pressing and cutting. Among them, there are no special requirements for the selection of negative electrode sheets, separators and electrolytes, which are all conventional choices in the field.

[0051] The technical solution provided by the present invention is described in detail below in conjunction with specific embodiments:

[0052] Unless otherwise specified, the reagents, materials and instruments used in the following examples are conventional reagents, conventional materials and conventional instruments in the art and can be obtained commercially. The reagents involved can also be synthesized by conventional methods in the art.

[0053] The ternary precursors used in the following examples and comparative examples are all selected from the same ternary precursor.

[0054] Embodiment 1,

[0055] A method for preparing an acidic ammonium salt-coated ternary positive electrode material comprises the following steps:

[0056] Ni 0.92 Co 0.06 Mn 0.02 The (OH)2 precursor and lithium hydroxide monohydrate were mixed evenly in a high-speed mixer according to a Li / (Ni+Co+Mn) molar ratio of 1.02, and then sintered at 500°C for 10 hours in a pure oxygen atmosphere to obtain a first-sintered material. The first-sintered material was mixed evenly with WO3 (0.5 mol%) in a high-speed mixer, and then sintered at 800°C for 7.5 hours in a pure oxygen atmosphere to obtain a second-sintered material, i.e., a high-nickel ternary positive electrode material.

[0057] Ammonium molybdate was added into a ball mill and ball milled for 1 hour to obtain ammonium molybdate powder. The powdered ammonium molybdate and high-nickel ternary positive electrode material were placed in a mixing tank at a ratio of 0.5:99.5, and mixed evenly using a high-speed mixer. The evenly mixed sample was transferred into a crucible, heated to 250°C, kept warm for 4 hours, and then heated to 550°C, kept warm for 6 hours to obtain the acidic ammonium salt-coated ternary positive electrode material.

[0058] The high-nickel ternary positive electrode material obtained in Example 1 was prepared into a positive electrode sheet, wherein the ratio of active material, binder and conductive carbon black was 95:2:3, and assembled into a 2032 button battery, and tested at 25°C in the 2.5~4.3V charge and discharge range.

[0059] Embodiment 2,

[0060] A method for preparing an acidic ammonium salt-coated ternary positive electrode material comprises the following steps:

[0061] Ni 0.92 Co 0.06 Mn 0.02 The (OH)2 precursor and lithium hydroxide monohydrate were mixed evenly in a high-speed mixer according to a Li / (Ni+Co+Mn) molar ratio of 1.02, and then sintered at 500°C for 10 hours in a pure oxygen atmosphere to obtain a first-sintered material. The first-sintered material was mixed evenly with WO3 (0.5 mol%) in a high-speed mixer, and then sintered at 800°C for 7.5 hours in a pure oxygen atmosphere to obtain a second-sintered material, i.e., a high-nickel ternary positive electrode material.

[0062] Add ammonium dihydrogen phosphate into a ball mill and obtain ammonium dihydrogen phosphate powder after ball milling for 1 hour. Put the powdered ammonium dihydrogen phosphate and high-nickel ternary positive electrode material in a mixing tank at a ratio of 1.25:98.75, use a high-speed mixer to mix them evenly, transfer the evenly mixed sample to a crucible, heat to 250°C, keep it warm for 4 hours, and then heat to 650°C, keep it warm for 6 hours, and then obtain the ammonium dihydrogen phosphate coated and modified high-nickel ternary positive electrode material.

[0063] The high-nickel ternary positive electrode material obtained in Example 2 was prepared into a positive electrode sheet, wherein the ratio of active material, binder and conductive carbon black was 95:2:3, and assembled into a 2032 button battery, and tested at 25°C in the 2.5~4.3V charge and discharge range.

[0064] Embodiment 3,

[0065] A method for preparing an acidic ammonium salt-coated ternary positive electrode material comprises the following steps:

[0066] Ni 0.92 Co 0.06 Mn 0.02 The (OH)2 precursor and lithium hydroxide monohydrate were mixed evenly in a high-speed mixer according to a Li / (Ni+Co+Mn) molar ratio of 1.02, and then sintered at 500°C for 10 hours in a pure oxygen atmosphere to obtain a first-sintered material. The first-sintered material was mixed evenly with WO3 (0.5 mol%) in a high-speed mixer, and then sintered at 800°C for 7.5 hours in a pure oxygen atmosphere to obtain a second-sintered material, i.e., a high-nickel ternary positive electrode material.

[0067] Powdered ammonium fluoride and high-nickel ternary positive electrode material are placed in a mixing tank at a ratio of 0.25:99.75, and are evenly mixed using a high-speed mixer. The evenly mixed sample is transferred to a crucible, heated to 350°C, and kept warm for 5 hours to obtain an ammonium fluoride-coated modified high-nickel ternary positive electrode material.

[0068] The high-nickel ternary positive electrode material obtained in Example 3 was prepared into a positive electrode sheet, wherein the ratio of active substance, binder and conductive carbon black was 95:2:3, and assembled into a 2032 button battery, which was tested at 25°C in the 2.5~4.3V charge and discharge range, wherein the ratio of active substance, binder and conductive carbon black was 95:2:3.

[0069] Embodiment 4,

[0070] A method for preparing an acidic ammonium salt-coated ternary positive electrode material comprises the following steps:

[0071] Ni 0.90 Co 0.08 Mn 0.02 The (OH)2 precursor and lithium hydroxide monohydrate were mixed evenly in a high-speed mixer according to a Li / (Ni+Co+Mn) molar ratio of 1.02, and then sintered at 500°C for 10 hours in a pure oxygen atmosphere to obtain a first-sintered material. The first-sintered material was mixed evenly with WO3 (0.5 mol%) in a high-speed mixer, and then sintered at 800°C for 7.5 hours in a pure oxygen atmosphere to obtain a second-sintered material, i.e., a high-nickel ternary positive electrode material.

[0072] Ammonium molybdate was added into a ball mill and ball milled for 1 hour to obtain ammonium molybdate powder. The powdered ammonium molybdate and high-nickel ternary positive electrode material were placed in a mixing tank at a ratio of 0.5:99.5 and mixed evenly using a high-speed mixer. The evenly mixed sample was transferred into a crucible, heated to 250°C, kept warm for 4 hours, and then heated to 550°C, kept warm for 6 hours, to obtain the ammonium molybdate coated modified ternary positive electrode material.

[0073] The high-nickel ternary positive electrode material obtained in Example 4 was prepared into a positive electrode sheet, wherein the ratio of active substance, binder and conductive carbon black was 95:2:3, and it was assembled into a 2032 button battery, which was tested at 25°C in the 2.5~4.3V charge and discharge range, wherein the ratio of active substance, binder and conductive carbon black was 95:2:3.

[0074] Embodiment 5,

[0075] A method for preparing an acidic ammonium salt-coated ternary positive electrode material comprises the following steps:

[0076] Ni 0.90 Co 0.08 Mn 0.02The (OH)2 precursor and lithium hydroxide monohydrate were mixed evenly in a high-speed mixer according to a Li / (Ni+Co+Mn) molar ratio of 1.02, and then sintered at 500°C for 10 hours in a pure oxygen atmosphere to obtain a first-sintered material. The first-sintered material was mixed evenly with WO3 (0.5 mol%) in a high-speed mixer, and then sintered at 800°C for 7.5 hours in a pure oxygen atmosphere to obtain a second-sintered material, i.e., a high-nickel ternary positive electrode material.

[0077] Add ammonium dihydrogen phosphate into a ball mill and obtain ammonium dihydrogen phosphate powder after ball milling for 1 hour. Put the powdered ammonium dihydrogen phosphate and high-nickel ternary positive electrode material in a mixing tank at a ratio of 1.25:98.75, use a high-speed mixer to mix them evenly, transfer the evenly mixed sample to a crucible, heat to 250°C, keep it warm for 4 hours, and then heat to 650°C, keep it warm for 6 hours to obtain the ammonium dihydrogen phosphate coated and modified high-nickel ternary positive electrode material.

[0078] The high-nickel ternary positive electrode material obtained in Example 5 was prepared into a positive electrode sheet, wherein the ratio of active substance, binder and conductive carbon black was 95:2:3, and it was assembled into a 2032 button battery, which was tested at 25°C in the 2.5~4.3V charge and discharge range, wherein the ratio of active substance, binder and conductive carbon black was 95:2:3.

[0079] Comparative Example 1

[0080] Ni 0.92 Co 0.06 Mn 0.02 The (OH)2 precursor and lithium hydroxide monohydrate were mixed evenly in a high-speed mixer according to a Li / (Ni+Co+Mn) molar ratio of 1.02, and then sintered at 500°C for 10 hours in a pure oxygen atmosphere to obtain a first-fired material. The first-fired material and WO3 (0.5 mol%) were mixed evenly in a high-speed mixer, and then sintered at 800°C for 7.5 hours in a pure oxygen atmosphere to obtain a second-fired material, i.e., a high-nickel ternary positive electrode material. The subsequent lithium-ion battery assembly steps are the same as those in Example 1.

[0081] The difference between this comparative example and Example 1 is that in this example, no subsequent coating is performed.

[0082] Comparative Example 2

[0083] The Ni0.90Co0.08Mn0.02(OH)2 precursor and lithium hydroxide monohydrate were mixed evenly in a high-speed mixer at a Li / (Ni+Co+Mn) molar ratio of 1.02, and then sintered at 500°C for 10h in a pure oxygen atmosphere to obtain a first-fired material. The first-fired material and WO3 (0.5 mol%) were mixed evenly in a high-speed mixer, and then sintered at 800°C for 7.5h in a pure oxygen atmosphere to obtain a second-fired material, i.e., a high-nickel ternary positive electrode material. The subsequent lithium-ion battery assembly steps are the same as those in Example 1.

[0084] The difference between this comparative example and Example 4 is that in this example, no subsequent coating is performed.

[0085] The high nickel ternary positive electrode material obtained in the embodiment and the comparative example is assembled into a button battery by adopting the technical scheme of preparing the positive electrode material into a lithium ion battery well known to those skilled in the art. The specific method is: the prepared high nickel ternary positive electrode material, conductive carbon black and polyvinylidene fluoride binder (PVDF) are weighed in a mass ratio of 95:2:3, mixed evenly, added with NMP to stir, and formed into a viscous slurry, and evenly coated on aluminum foil, and then vacuum baked at 80°C, pressed, and cut into a positive electrode sheet with a diameter of 14 mm. A pure lithium sheet with a diameter of 16 mm is used as the negative electrode sheet, a mixed solution of LiPF6+DEC / EC (volume ratio 1:1) is used as the electrolyte, and a polypropylene microporous membrane is used as the diaphragm, and the button battery is assembled in a glove box filled with argon.

[0086] Explanation of the capacity retention rate test: Using the Xinwei test cabinet (CT-4008-5V10mA 80CH), at 25°C, the cycle voltage is 2.5~4.3V, the constant voltage cut-off current is 0.062mA, and the current density is 0.5C, and the cycle is performed for 40 cycles.

[0087] Table 1. Test results of positive electrode materials of Examples 1-5 and Comparative Examples 1-2

[0088]

[0089] Combined with reference Figure 1-Figure 14 According to Table 1, Figure 1 and Figure 2 It can be seen that compared with Comparative Example 1, after being coated with acidic ammonium salt, the contents of Li2CO3, LiOH and total residual alkali in the positive electrode active materials provided by Examples 1-3 decreased, and a uniformly coated positive electrode material was obtained, thereby having excellent capacity. Compared with Comparative Example 2, after being coated, the contents of Li2CO3, LiOH and total residual alkali in the positive electrode active materials provided by Examples 4-5 also decreased, and a uniformly coated positive electrode material was obtained. Figure 3-Figure 9 It can be seen that after being coated with acidic ammonium salt, a ternary positive electrode material with more uniform particle morphology is obtained. Figure 10-Figure 14From the EDS test analysis, it can be seen that after being coated with acidic ammonium salt, the required coated elements are evenly coated on the surface of the ternary positive electrode material.

[0090] In summary, in the preparation method of the acidic ammonium salt-coated ternary positive electrode material provided by the present invention, by adding the acidic ammonium salt as a coating additive, the acidic ammonium salt can undergo an acid-base neutralization reaction with the Li2CO3 and LiOH remaining on the surface of the di-sintered material, thereby effectively reducing the residual alkali of the di-sintered material; the coating additive can be evenly mixed after ball milling for sintering and coating; the added acidic ammonium salt has a low melting point, so that the coating additive can be converted into a liquid at a lower temperature of the second-stage calcination, and the liquid coating additive is evenly distributed on the surface of the ternary positive electrode material in a film-like morphology, which can achieve maximum coating coverage, make the coating uniform, improve its coating effect, and improve the cycle stability of the lithium-ion battery.

[0091] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made by using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A method for preparing an acidic ammonium salt-coated ternary positive electrode material, characterized in that: The specific steps include: S1. After the ternary precursor and lithium hydroxide monohydrate are uniformly mixed in a high-speed mixer, sintering is performed at 400° C. to 600° C. for 6 h to 12 h in a pure oxygen atmosphere to obtain a sintered material; S2, mixing the first-fired material and the dopant in a high-speed mixer, and sintering at 400° C. to 1000° C. for 6 h to 12 h in a pure oxygen atmosphere to obtain a second-fired material; S3, ball-milling the coating additive to obtain a powdered coating additive, wherein the coating additive is ammonium molybdate; S4, mixing the sintered material in S2 and the coating additive in S3 uniformly by a high-speed mixer; S5, calcining the mixture in S4 in two stages, calcining at 200°C-300°C for 4h-6h, and then raising the temperature to 400°C-800°C for 6h-12h to obtain an acidic ammonium salt-coated ternary positive electrode material; Wherein, in S1, the ternary precursor is Ni a Co b Mn 1-a-b (OH)2 or Ni a Co b Mn c X 1-a-b-c (OH)2, wherein a, b, c are any numbers between 0 and 1, and X is a doping element, including any one of Nb, Zr, Cr, Mo, Ti, W and V; the addition ratio of Li / (Ni+Co+Mn) in the ternary precursor and lithium hydroxide monohydrate is 1.00-1.05; In S2, the dopant is an oxide of any one of Nb, Zr, Cr, Mo, Ti, W and V, and the content of the dopant is 0.2wt% to 2wt%; In S3, the ball milling time of the coating additive is 30 min to 120 min, the ball milling speed is 500 rpm to 1500 rpm, and the content of the coating additive is 0.2 wt% to 2 wt%.

2. An acidic ammonium salt-coated ternary positive electrode material, characterized in that: The material is prepared by the method for preparing the acidic ammonium salt-coated ternary positive electrode material according to claim 1.

3. A lithium ion battery, characterized in that: It comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet comprises the acidic ammonium salt-coated ternary positive electrode material according to claim 2.

Citation Information

Patent Citations

  • Ternary cathode material with surface reaction covered and preparing method of ternary cathode material

    CN108011100A

  • Garnet-type ion conductor-coated high-nickel ternary positive electrode material, preparation method and lithium ion battery obtained by preparation

    CN109904427A